An Educational Inspectorate for Five Continents - Tuduri Vila, Camila (Avances en Supervisión Educativa, 2026)
This article analyses the role of the Central Inspectorate of the Ministry of Education, Vocational Training and Sports within the framework of Spanish educational action abroad, understood as a manifestation of the internationalisation of the education system. To this end, it describes its regulatory and organisational framework, as well as the typology and geographical distribution of the centres and programmes under its supervision. The study examines the main constraints and distinctive features of its activity. Finally, several areas for improvement are identified, focusing on the systematisation of information derived from inspection activities, the strengthening of communication mechanisms with centres and programmes, and the development of specific competencies for operating in international contexts.